The Product Development with Cultural Capital for The Positive Community of the Ban Thonmai Mat Weaving Group,Muang Khon Kaen District,Khon Kaen Province - นาชัยสินธุ์ ดวงจันทร์ (Journal of Fine and Applied Arts Khon Kaen University, 2019)
The research methodology of the study included qualitative research which focused on participatory research, in-depth interview with experts and specialists, field survey, and data analysis for the potentiality of the Ban Thonmai Mat weaving group.Cultural capital, which includes local materials; wisdom; and specialties, has been considered valuable cultural assets whose uniqueness that conforms to the way of life should be conserved. The improvement of the old products and the development of the new ones were made specially participatory and different from any other areas by the traditional wisdom that has been used in the development of modern wisdom from the cultural capital. A collection of the products entitled ‘Heart-woven bond of Nonthon’ was made from threads and rush plant, which are ones of the local materials. These products have been made as the community’s signature products that are produced from cultural capital of the positive community. Based on the imagination,the products were created uniquely to introduce the customers the brand’s image which are attractive, beautiful, and positive; so as to establish the reliability of the products. Research found that,The community’s products includes partitions and lamps made from rush mats with unique and stylish patterns which are woven from rush plants and threads. This weaving technique using rush plants and threads is a skill of local artisans, who are a part of the community product development.